Determination of ionizing threshold of trimethylamine ions with a high resolution RGA mass spectrometer. (1st February 2022) - Trindade, A.M.F.; Escada, J.; Rajado Silva, M.; Borges, F.I.G.M.; Santos, F.P.
Abstract: In this work, a mass spectrometer residual gas analyzer (RGA) was used to determine the ionization thresholds (ionization energy and appearance energy) in trimethylamine (TMA, (CH3 )3 N), as well as the relative abundance of the ions produced by electron impact in the 7.5–70 eV electron energy range. The ten most intense peaks in the RGA mass spectra, corresponding to the most abundant ions formed by electron impact at 70 eV in TMA, were analyzed. The ionization energy for TMA, as assessed by this experiment, is 7.9 ± 0.2 eV and it is the threshold of formation of the C3 H9 N + ion. This ion species is the most abundant one below 18 eV electron impact energy, being surpassed by the C3 H8 N + ion above this energy. In order to assess the method used, methane (CH4 ), whose ionization properties are well established, was previously studied. The agreement between the results obtained for CH4 and those found in the literature provided the validation of the experimental method used in this work.